Analysis of Student Mathematics Learning Results Using the Problem Based Learning Model - Hasibuan, Syarinah Junianti; Anim, Anim (Holistic Science, 2024)
Student learning outcomes are a measure of student success in the learning process in class. This research aims to analyze student learning outcomes in class VII-5 of SMP Negeri 5 Kisaran in mathematics subjects. The type of research carried out was qualitative with a qualitative descriptive method. The research subjects were students in class VII-5 of SMP Negeri 5 Kisaran with a total of 32 people. The analysis technique used in this research is a qualitative descriptive data analysis technique including data reduction, data display, and verification. The results of this research show that the learning outcomes of students with low criteria were 2 students, medium as many as 17 students, high as many as 12 students, and very high as many as 1 student and the average score obtained by students in mathematics learning activities was 20.88 with a percentage 84%, which means that the mathematics learning carried out by students in class VII-5 at SMP Negeri 5 Kisaran is in the good category.